Harnessing nature’s ingenuity: A comprehensive exploration of nanocellulose from production to cutting-edge applications in engineering and sciences - Nurhanis Sofiah, Abd Ghafar; Pasupuleti, Jagadeesh; Samykano, Mahendran; Kadirgama, Kumaran; Koh, Siaw Paw; Tiong, Sieh Kieh; Pandey, Adarsh Kumar; Yaw, Chong Tak; Natarajan, Sendhil Kumar (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Primary material supply is the heart of engineering and sciences. The depletion of natural resources and an increase in the human population by a billion in 13 to 15 years pose a critical concern regarding the sustainability of these materials; therefore, functionalizing renewable materials, such as nanocellulose, by possibly exploiting their properties for various practical applications, has been undertaken worldwide. Nanocellulose has emerged as a dominant green natural material with attractive and tailorable physicochemical properties, is renewable and sustainable, and shows biocompatibility and tunable surface properties. Nanocellulose is derived from cellulose, the most abundant polymer in nature with the remarkable properties of nanomaterials. This article provides a comprehensive overview of the methods used for nanocellulose preparation, structure–property and structure–property correlations, and the application of nanocellulose and its nanocomposite materials. This article differentiates the classification of nanocellulose, provides a brief account of the production methods that have been developed for isolating nanocellulose, highlights a range of unique properties of nanocellulose that have been extracted from different kinds of experiments and studies, and elaborates on nanocellulose potential applications in various areas. The present review is anticipated to provide the readers with the progress and knowledge related to nanocellulose. Pushing the boundaries of nanocellulose further into cutting-edge applications will be of particular interest in the future, especially as cost-effective commercial sources of nanocellulose continue to emerge.